Description of Anxiety in Preoperative Cesarean Section Patients with Spinal Anesthesia in the Central Surgical Installation at RS TK IV Cijantung Kesdam Jaya in 2023 - Yohana Saputra (Westscience Press, 2023)
Preoperative anxiety is an anticipatory response to an experience that is considered by the patient as a threat in the role of life, body integrity, and even life itself (Agustin, 2020). Influential factors are husband's support, postpartum complications, age, parity, and type of SC (Irawati, 2017 in Imani, 2020). The sources of preoperative anxiety are broadly divided into two, namely anxiety about anesthesia and anxiety about surgical procedures. (Jawaid M et.al, 2016). Spinal anesthesia techniques can be performed in Sectio Caesarea with the main advantages of this technique are the risk of aspiration in the mother is lower, the baby is not exposed to drugs that cause respiratory depression, the patient remains conscious during surgery and maintains the airway, and requires minimal postoperative and analgesia treatment (Morgan, 2013). This study aims to describe the level of anxiety of preoperative Sectio Caesarea patients with spinal anesthesia at the Bhayangkara Public Hospital. Method of Research: This study was a descriptive survey with a cross sectional design conducted from February to March 2022. The population in this study was 208 patients with a sample of 32 patients. The sampling technique used in this research is Quota Sampling. The results of this study were 43.8% of respondents experienced mild anxiety. In the age group less than 30 there are 25% of patients who experience moderate anxiety. The results of the study indicate that at all levels of education, respondents generally experience mild anxiety and it is also found that at the level of experience, respondents generally experience mild anxiety. More than half (56.3%) of respondents were under 30 years old with the dominant education level of respondents being high school (46.9%). Almost half (43.8%) of respondents who underwent cesarean section surgery with spinal anesthesia at the Bhayangkara Public Hospital experienced mild anxiety.